2008
DOI: 10.1021/nl080452q
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Scale In-situ Observation of Carbon Nanotube Growth from Solid State Iron Carbide Nanoparticles

Abstract: We have first observed the nucleation and growth process of carbon nanotubes (CNTs) from iron carbide (Fe 3C) nanoparticles in chemical vapor deposition with C 2H 2 by in situ environmental transmission electron microscopy. Graphitic networks are formed on the fluctuating iron carbide nanoparticles, and subsequently CNTs are expelled from them. Our atomic scale observations suggest that carbon atoms diffuse through the bulk of iron carbide nanoparticles during the growth of CNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
531
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(562 citation statements)
references
References 32 publications
26
531
2
3
Order By: Relevance
“…Although the VLS model reasonably explains the phase separation dynamics between carbon and iron, it is still controversial whether SWNT growth always requires the formation of metal carbide or not. Indeed, it is likely that this depends on the type of the metal catalyst employed (see for instance two environmental transmission electron microscopy (ETEM) studies where cap nucleation was observed, one where bulk iron carbide was formed [27] and another where nickel did not form carbide in bulk [28]). Since the VLS model is a concept mainly based on thermodynamic reasoning, it does not promote per se an understanding of the atomistic details of the SWNT nucleation and growth processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the VLS model reasonably explains the phase separation dynamics between carbon and iron, it is still controversial whether SWNT growth always requires the formation of metal carbide or not. Indeed, it is likely that this depends on the type of the metal catalyst employed (see for instance two environmental transmission electron microscopy (ETEM) studies where cap nucleation was observed, one where bulk iron carbide was formed [27] and another where nickel did not form carbide in bulk [28]). Since the VLS model is a concept mainly based on thermodynamic reasoning, it does not promote per se an understanding of the atomistic details of the SWNT nucleation and growth processes.…”
Section: Introductionmentioning
confidence: 99%
“…An interface between carbon nanotubes and metal particles was also observed during the growth of nanotubes from catalytically active metals (11). However, the structure of the interface and the nature of bonding between metal and carbon remained unclear.…”
mentioning
confidence: 99%
“…41,[50][51][52][53] Hence, E-TEM enabled the direct measurement of CNT growth kinetics of individual CNTs growing from a single catalyst nanoparticle, as shown in Fig. 6.…”
Section: Catalytic Activation and Cnt Nucleationmentioning
confidence: 99%